Body composition analysis in patients with Hashimoto’s disease and vitamin D deficiency (Journal of Medical Science, 2024)
Introduction. Hashimoto thyroiditis (HT) is one of the most common organ-specific autoimmune diseases. This autoimmune response disrupts thyroid function, affecting biochemical processes and metabolism, with symptoms often including weight gain and easy fatigue. Vitamin D has so far been considered only a key regulator of calcium-phosphate metabolism. However, it is now considered a pleiotropic substance and increasingly published data indicate that it also plays a role in immune modulation and metabolic health. Aim. The study aimed to assess anthropometric measures, body composition, and muscle strength in patients with HT, correlate these parameters with serum 25(OH)D levels, and evaluate the impact of vitamin D supplementation. Material and Methods. The study included 80 female patients, aged ≥18 years, divided into an HT group (n=51) and a Control Group with non-toxic diffuse or nodular goiter (n=29). Vitamin D supplementation was administered based on the initial 25(OH)D concentration, at a dose of 6000 IU or 4000 IU daily for 3 months to patients with 25(OH)D concentration < 20 ng/ml and ≥ 20 ng/ml, respectively. Anthropometric and body composition measurements, as well as blood tests for 25(OH)D, TSH were performed at baseline and after supplementation. Results. Both groups showed significant increases in 25(OH)D levels post-supplementation. In the HT group, lean body mass and muscle strength improved significantly (p = 0.002 and p = 0.02, respectively). In the Control Group, muscle strength increased (p = 0.01) and hip circumference decreased slightly (p = 0.03). No significant differences were found in body composition between the groups, although women with HT had larger hip circumferences. Correlation analysis revealed a moderately strong inverse relationship between baseline 25(OH)D levels and BMI in the Control Group (R = -0.44; p = 0.04), with no other significant associations identified. Conclusions. Vitamin D supplementation effectively increased serum 25(OH)D levels and improved muscle strength and lean body mass in women with HT. Further research is needed to explore the mechanisms by which vitamin D may impact metabolic and immune health in HT patients.